2016
DOI: 10.1117/1.jbo.21.12.121502
|View full text |Cite
|
Sign up to set email alerts
|

Hybridized wavefront shaping for high-speed, high-efficiency focusing through dynamic diffusive media

Abstract: shaping for high-speed, highefficiency focusing through dynamic diffusive media," J. Abstract. One of the prime limiting factors of optical imaging in biological applications is the diffusion of light by tissue, which prevents focusing at depths greater than the optical diffusion limit (typically ∼1 mm). To overcome this challenge, wavefront shaping techniques that use a spatial light modulator (SLM) to correct the phase of the incident wavefront have recently been developed. These techniques are able to focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…To measure the actual system latency, we used our DOPC system to focus light through a dynamic scattering medium with controllable speckle correlation times, achieved using a moving sample strategy [14,15,23,36,38,5355]. The scattering sample was a 3 mm thick slice of fresh chicken breast tissue (scattering coefficient μ s = 30 mm −1 , scattering anisotropy g = 0.965 [23]), sandwiched between two microscope slides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the actual system latency, we used our DOPC system to focus light through a dynamic scattering medium with controllable speckle correlation times, achieved using a moving sample strategy [14,15,23,36,38,5355]. The scattering sample was a 3 mm thick slice of fresh chicken breast tissue (scattering coefficient μ s = 30 mm −1 , scattering anisotropy g = 0.965 [23]), sandwiched between two microscope slides.…”
Section: Resultsmentioning
confidence: 99%
“…This moving sample strategy has been used in previous works [14,15,23,36,38,5355]; however, it cannot be excluded that the decorrelation caused by a moving scattering medium is subtly different from the decorrelation caused by living biological tissue or other dynamic scattering media such as fog and turbid water.…”
Section: Discussionmentioning
confidence: 99%
“…Holographic techniques [13] can achieve fast focusing in few dozens of milliseconds with an optical resolution, but the imaging remains limited at intermediary depths, where light is not completely multiply scattered. Iterative wavefront optimization [14] has no fundamental limitations in reaching the optical resolution or in depth but is intrinsically slow, and technical developments are requested to accelerate the process [15,16,17]. In these systems, one iteration takes long between 0.12 to 10 ms. Iterative wavefront shaping uses feedback algorithms, which consist on the selection of a SLM spatial mode (one or many pixels), the application of phase shifts between 0 and 2 for this mode and the determination of the phase that maximizes a merit factor of the intensity pattern (e.g.…”
mentioning
confidence: 99%
“…Compared to previous closed-loop implementations, one mode is optimized 37 times faster [17]. A faster setup, albeit open loop, has been described in the literature [16] (0.125 ms/mode). As a proof of principles, we have shown that our setup allows refocusing scattered light within fast decorrelating samples, with timescales of decorrelation as small as 30 ms.…”
mentioning
confidence: 99%
“…To overcome this optical diffusion limit and achieve deep-tissue non-invasive optical imaging, manipulation, and therapy, [3][4][5][6][7][8][9] wavefront shaping techniques, including feedbackbased wavefront shaping, [10][11][12][13] transmission matrix measurement, [14][15][16][17] and optical time reversal/optical phase conjugation (OPC), [18][19][20][21][22][23][24][25][26][27][28] are being actively developed. By modulating the wavefront of the incident light, the phase delays among various optical paths are compensated, and optical focusing (by constructive interference) can be achieved through scattering media.…”
mentioning
confidence: 99%